Angka kebuntingan sapi perah dengan korpus luteum persisten setelah pemberian kombinasi prostaglandin F2α dan gonadotropin - Azwani, Nabila; Srianto, Pudji; Madyawati, Sri Pantja; Sardjito, Trilas; Suprihati, Endang (Ovozoa: Journal of Animal Reproduction, 2021)
This case study aims to determine the effect of a combination of prostaglandin F2α (PGF2α) with Gonadotropin (PG-600), and human chorionic gonadotropin (hCG) on the estrus and pregnancy rates in Holstein Friesian (HF) cows with persistent corpus luteum (PCL). A total of 15 Holstein Friesian (HF) dairy cows aged 3-5 years with body condition score (BCS) 5-7 (scale 1-9) diagnosed with PCL, were injected with 7.5 mg PGF2α intra-vulvar submucosa. Cows were then divided into three treatment groups. Group P0 was not given the combination treatment, while P1 group was injected with a  combination of 300 IU PG-600 and 150 IU hCG, meanwhile P2 group was was injected with a combination of 300 IU PG-600 and 300 IU hCG intra-muscularly. The PGF2α and PG-600 injections were carried out on the same day PCL was diagnosed. Meanwhile, the injection of hCG was carried out at the same time as the AI. The Pregnancy examination was performed 90 days after AI through rectal palpation. The results showed that all treated cows were estrus  observed with the fastest onset of estrus was the P2 group, that was significantly different (p <0.05) compared to the P0 and P1 groups. All treated cows were diagnosed as pregnant. It can be concluded that the administration of PGF2α or its combination with gonadotropins in HF cows with PCL could result in 100% estrus and pregnancy rates.